Rancang Bangun alat pembuka pintu portal berbasis arduino menggunakan smartphone - Achmad Haris Afandi; Putri Anbar Ghalia; Kistiani Kistiani; Indri Rahma Sari; Sri Aswaidar Miza (Navigation Physics : Journal of Physics Education, 2019)
This study aims to design a prototype Arduino-based portal door controller system device using a smartphone. The making of the tool is done as one of the efforts in advancing technology to provide convenience and comfort through the development of an automated system in the home in the form of automatic portal doors using smartphones. The components used for system design are Arduino REV3 microcontroller module, USB 2.0 type A / B cable (Arduino USB cable), SG90 9g servo motor, red and green LEDs, 220Ω resistor, mini protoboard, connecting cable, jumper cable, and bluetooth module HC06, Powerbank with a capacity of 5600 mAh and a smartphone, while designing software uses Arduino IDE. Based on the results of measurements and testing, the system on the device made is able to open and close the portal door automatically at a maximum distance of 15 meters with a maximum response time of 1 second in open space